Investigating food limitations in wild fisheries: Estuarine fish form dynamic aggregations around a supplementary feeding station and increase localised secondary productivity. (January 2022) - Cook, Denham G.; Jaksons, Peter; Alavi, Maryam; Jerrett, Alistair
Abstract: Whether wild fish populations are food limited in some inshore and estuarine marine ecosystems is an area of increasing research and focus. To investigate this phenomenon, the abundance and behaviours of fish in a temperate South Pacific estuary were observed in response to the provision of supplementary feed. Observations were conducted over 120-weeks, involving a 60-week period over which fish were actively fed followed by a 60 week without feeding. During active feeding, estuarine associated fish (primarily yellow-eyed mullet Aldrichetta forsteri ) showed a highly predictable pattern of fish abundance, biomass and behavioural formation coinciding with the almost daily feeder operation. Tidal current velocities and turbidity appeared to have little influence on the attendance and formations of fish over this period, although season did influence some variables. Peaking at close to 9000 individual fish and 880 kg biomass, fish attendance during the operation of the feeding station was markedly higher than during the period when the feed station was no longer active. Whereby only 0–100 individuals were typically present, and fish no longer showed collective behavioural formations. A direct result of the large number of fish aggregating on this feeding station was an increase in the secondary productivity of the observable zone around the feeding station. Whereby secondary productivity increased by a factor of ∼30 above that observed when the feed station was not operating. Supplementary feeding effectively transformed the study site – a highly modified intertidal location – from an area of very low productivity to one comparable with highly productive temperate estuary environments described elsewhere. The behavioural drivers and ecological relevance of these observations are discussed. Highlights: Wild fish populations have been identified to be food limited in their natural environment. This phenomenon was investigated by providing supplementary food in a South Pacific Estuary. Behavioural aggregations, increases in fish abundance and secondary productivity, were observed. These observations present further support for the food limitation hypotheses. Outcomes also identify novel approaches to support fisheries and nearshore ecologies.